The Relationship Between Corporate Social Responsibility (CSR) and FINANCIAL PERFORmance in a Company - Romadhon, Moch Iqbal; Putri, Nabila Amelia; Hwihanus, Hwihanus (CV. Lenggogeni Data Publishing, 2024)
Corporate financial performance, or CFP, and corporate social responsibility are linked concepts. CSR enhances employee productivity and fosters collaboration among peers. Financial performance and corporate social responsibility have a favorable correlation. Depending on whether there was a good or negative association between CSR and financial success, we may draw conclusions from our investigation's findings. We selected, aggregated, perused five papers titled